SOUND OF PADDLE WHEEL ON SEA BASS GROWTH - Sunardi Sunardi; Anton Yudhana; Ahmad Syahril Mohd Nawi; Jafri Din; Saberi Mawi (Universitas Ahmad Dahlan, 2009)
The objective of this research is sound effect for brackish water for Sea bass (Cynoscion nobilis). Breeding farm 25x100m, 2m of depth, and 6 paddle wheels which generate the sound are available for research. Sound profile has been measured to investigate the amplitude at various measurement points at various depths by using Cetacean hydrophone C304. The output of hydrophone has been analyzed by using SpectraPlus software. For the second measurement, two cages which size 3x3m have been used for life fish habitat. Then, fish put in the edge cage (20), center cage (20), and out of cage (12500). Sound profile has been measured for position-based (edge/center cage), time-based (morning/noon/evening), and point-based. Time series, spectrum frequency, and phase have been analysis. Fish growth progress has been monthly measured at every cage. Fish in the cage is growth as linearly, while fish growth for out of cage is exponentially. Size and weight of fish in the both cages is less than out of cage. This research concludes that sound have no significantly effect for fish growth. Limited mobility to look for food and stress are more influences to fish growth than sound effect.